Impact of Prebiotic β-glucan Treatment at Juvenile Age on the Gut Microbiota Composition and the Eventual Type 1 Diabetes Onset in Non-obese Diabetic Mice - Taylor, Harrison B.; Vasu, Chenthamarakshan (Frontiers in Nutrition, 2021)
Complex dietary polysaccharides such as β-glucans are widely used for their anti-inflammatory properties. We reported before that oral administration of Yeast β-glucan (YBG) in adult mice can help delay type 1 diabetes (T1D) onset and suppress gut inflammation, through modulation of the structure and function of gut microbiota. Since juvenile age is characterized by profoundly changing immature gut microbiota, we examined the impact of oral treatment with YBG in non-obese diabetic (NOD) mice at this age. Juvenile mice that received daily oral administration of YBG starting at 15-days of age for 7 or 30 days were examined for changes in gut microbiota, immune characteristics and T1D incidence. Mice that received YBG for 30 days, but not 7 days, showed considerable changes in the composition and diversity of fecal microbiota as compared to controls. Predictive functional analysis, based on 16S rDNA sequences, revealed overrepresentation of glycan biosynthesis and metabolism, energy metabolism, and fatty acid biosynthesis pathways in mice that received YBG for thirty days. Immune phenotype of the colon showed skewing towards immune regulatory and Th17 cytokines with increases in IL10, IL17, and IL21 and a decrease in TNFα. Most importantly, mice that received YBG treatment for 30 days showed significantly suppressed insulitis and delayed onset of hyperglycemia compared to controls. Overall, this study suggests that oral consumption of YBG beginning at prediabetic juvenile ages could have positive maturational changes to gut microbiota and immune functions and could result in a delay in the disease onset in those who are predisposed to T1D.